Aspek Hukum dalam Penyelenggaraan Bisnis Perhotelan - Hernawati RAS; Dani Durahman (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The development of the law as part of a national development known as law reform is carried out thoroughly and integratedly. The hospitality business is growing rapidly as the economy develops, within the restrictions on the scope of the Hotel's business, there is a legal device that regulates the permit and protection of consumers. Hospitality businesses that do not have amdal permits Environmental law enforcement can be done by sanctioning administrative sanctions. Administrative sanctions, settlement of environmental issues outside the court and even criminal sanctions have been stipulated in Law No. 32 of 2009. The aspect of protection to Hospitality Consumers must be in accordance with the provisions of Law No. 8 of 1999, hospitality business must provide legal certainty in providing protection to consumers where currently there are still many hotels that do not provide information about consumer rights and obligations and the development of social responsibility (social responsebility).